New RTD-Based General Threshold Gate Topologies and Application to Three-Input XOR Logic Gates - S. M. Mirhoseini; M. J. Sharifi; D. Bahrepour (Journal of Electrical and Computer Engineering)
This paper presents two new general threshold gate (GTG) structures which are based on the monostable-bistable element (MOBILE) as their main part. These new GTGs eliminate an RTD from the structure compared to old structures and lead to less elements count and better performance in terms of power consumption, maximum frequency, and power-delay product (PDP). In the paper also two new single gate three-input XOR logic gates based on the old GTGs and two ones based on the new GTGs are presented and simulated in HSPICE simulator.